A â€œRole Modelâ€ Leader and Itâ€™s Impact to Job Performance - Wulandari, Wilia Desi; Putri, Vini Wiratno (Management Analysis Journal, 2020)
The purpose of this research is to know the influence of authentic leadership towards employees' performance through OCB. The population in this study is nurse with civil servants status at RSJD Dr. Amino Gondohutomo. Methods of collecting data using interviews and questionnaires. The sampling technique uses a simlpe random sampling. Sample is 109 nurses. Data analysis methods use descriptive analysis and analysis using SmartPLS 3.0. The results showed that there was a significant negative relationship between authentic leadership towards employee performance. There is a positive and significant relationship between authentic leadership towards creativity and organizational citizenship behaviour as well as creativity and organizational citizenship behaviour towards employee performance. In addition, research results also show that the creativity and behavior of the organizational citizenship of the employee has a significant positive impact on the employee's performance. The advice for the organization is to strengthen the relationship between leaders and nurses and increasing the information in the field of nursing that can trigger the emergence of creativity in work. For further research it is recommended to increase the number of research samples.